142k views
3 votes
WILL GIVE E BRAINLLY TO THE ONE THAT MAKES SENSE

1. Solve using the elimination method. Show your work!

2x – y = 6

x + y = 6 Solution: ( , )


2. Is (3, -2) the solution to this system of equations? Yes or No (circle one)

Show how you determined your answer.

-2x – 4y = 2

3x + 4y = 8

1 Answer

7 votes

Answer:

NO

Explanation:

Let's solve the system

2x – y = 6

x + y = 6

using the elimination method. Note that -y and y cancel, so if we combine these two equations, we end up with 3x = 12, and thus x = 4.

Subbing 4 for x in the 2nd equation, we get 4 + y = 6, and thus y = 2.

The solution is (4, 2).

NO: (3, -2) IS NOT THE SOLUTION TO THIS SYSTEM.

User Ganesh Manickam
by
5.2k points